Platelet Indices as Potential Monitoring Biomarkers in COVID-19: A New Hope - Attika Khalid, Sami Saeed, Madeeha Rehan, Nadia Arif, Attika Khalid, Sami Saeed, Madeeha Rehan, Nadia Arif (Journal of Rawalpindi Medical College, 2021)
Objective: To investigate the relationship between established acute inflammatory markers in COVID-19 patients with Mean platelet volume (MPV) and Platelet large cell ratio (P-LCR). Materials and Methods: This was a retrospective longitudinal study conducted at Fauji Foundation Hospital, Rawalpindi from 10th June to 10th August 2020. Biochemical parameters i.e. CRP, serum ferritin, LDH, and pro-BNP as well as hematological parameters (MPV and P-LCR) were noted once every week during admission of all the COVID-19 positive patients. Data were analyzed using IBM-SPSS version 23. Repeated measure ANOVA using a generalized linear model was done to check the trend of values during the duration of their stay. Pearson Correlation analysis and regression models were estimated to check the relationship of MPV and P-LCR with C- reactive protein, serum Ferritin, LDH, and pro-BNP. P-values less than 0.05 were considered statistically significant. Results: The mean age of the studied group was 55.47 (SD=±15.0) years with the female to male ratio being 2:1. Mean platelet volume showed a statistically significant positive correlation with the established set of inflammatory markers other than pro-BNP with a p-value of less than 0.05.P-LCR however showed a positive correlation with CRP (p-value of less than 0.05) only with no significant correlation with other biochemical markers. Conclusion: MPV is reported on routine complete blood count report (CBC). It is readily available at even the most under-resourced health centers; therefore reporting the platelet indices does not require extra testing, sampling, or reagent cost. A statistically significant positive correlation amongst the established acute inflammatory markers and relatively understudied platelet indices (MPV) in COVID-19 provides a cost-effective, readily available, and time-efficient tool for marking disease progression.